Facile synthesis of HPW@MOF-199 embedded in SBA-15 functionalized with -COOH groups as a steady catalyst for the esterification reaction. (15th May 2023) - Zhang, Yibo; Wang, Wei; Liu, Chunlai; Shen, Peihang; Liu, Zelong; Hu, Jianglei; Shi, Fengwei
Graphical abstract: Highlights: The carboxyl group functionalized SBA-15 was prepared by one-pot co-condensation. HPW@MOF-199 crystals grown in situ inside the SBA-15C pore. HPW@MOF-199@SBA-15C retained the ordered 2D hexagonal mesoporous structures. HPW@MOF-199@SBA-15C showed good catalytic performance in esterification reactions. HPW@MOF-199@SBA-15C had the excellent stability. Abstract: In this work, we successfully synthesized a novel composite (HPW@MOF-199/SBA-15C, PMS-15C) in which MOF-199 encapsulated HPW catalyst (named HPW@MOF-199) was confined in SBA-15C, which is the carboxy-functionalized SBA-15. Physicochemical properties of the composites PMS-15C were systemically characterized by N2 adsorption–desorption isotherms, wide-angle and low-angle XRD, XPS, FT-IR, SEM, and TEM. The results exhibited that HPW@MOF-199 had been successfully synthesized and embedded into the SBA-15C pores by COOH on the surface of SBA-15C. Meanwhile, the composites PMS-15C exhibited high activity and excellent reuse properties in the esterification reaction of acetic acid and ethanol, and no evidence of aggregation, leaching, or inactivation of HPW@MOF-199 during repeated use. The good dispersion of HPW within the MOF-199 cage and the interaction between HPW@MOF-199 and SBA-15C may be responsible for the good catalytic activity as well as the high stability of PMS-15C.